Phytotherapy as an alternative for treating fish disease - Valladao, G. M. R. [UNESP]; Gallani, S. U. [UNESP]; Pilarski, F. [UNESP] (Wiley-Blackwell, 2015)
Intensification of livestock rearing often promotes an increase in inappropriate practices that disregard care for the environment, animal health, and workers' health. Intensive fish farming systems are often associated with higher stocking density and massive use of artificial feed. Currently, outbreaks of parasitic, bacterial, and fungal diseases act as major limiting factors for fish farming, meaning that producers have to make use of massive amounts of antibiotics, disinfectants, and pesticides in order to control mortality and avoid huge economic losses. Because of adverse effects on the aquatic environment, terrestrial organisms, and human health (both fish handlers and consumers), this therapy has been criticized. Use of herbal medicines within animal production has shown promise, in that it is natural and biodegradable and has antimicrobial activity against various pathogens, including those relating to fish. Recently, researchers have reported promising effects from many herbal medicines for treating parasitic diseases caused by protozoa and metazoa, and broad activity against bacteria and fungi. This review addresses the current issues regarding indiscriminate use of chemicals and antibiotics in aquaculture and discusses the main findings and methodologies of the latest research on herbal medicines to stimulate and accelerate research in this field, especially in developing countries.